Effect of Different Drying Procedures on the Nutritional Value of the Mantle and Tentacles of Sepia officinalis. (14th August 2017) - Tir, Meriam; Bejaoui, Safa; Chetoui, Imene; Mejri, Hssan; Zaaraoui, Abderrazzek; El Cafsi, Afif; El Cafsi, Mhamed
Abstract: The aim of this work was to investigate the influence of two different drying methods, traditionally by sun and controlled temperatures of 45, 50, 60 and 70 °C and relative humidity of 20 and 30% on the chemical composition of Sepia officinalis . When compared to fresh samples, lipid content increased under both drying methods whereas protein levels significantly increased only under controlled conditions. Drying procedures increased the percentage of saturated fatty acids mainly in sun‐dried samples and at high temperature (70 °C). A significant decrease in the amount of polyunsaturated fatty acids was detected in sun‐dried samples. No significant differences were found between the levels of polyunsaturated fatty acids of fresh cuttlefish and those under controlled conditions. The highest value of malondialdehyde in mantles was observed in sun‐dried samples, while in tentacles the highest level was seen at 70 °C. The highest level of advanced oxidation protein products was noted in traditionally sun‐dried samples. The results obtained showed that 45–50 °C and 20–30% humidity conserved the value of proteins and lipids more than traditional drying. Results of this study may be suitable for developing a reliable industrial index.